2016
DOI: 10.1080/0305764x.2015.1118440
|View full text |Cite
|
Sign up to set email alerts
|

Governing food choices: a critical analysis of school food pedagogies and young people’s responses in contemporary times

Abstract: Recently a proliferation and intensification of school programmes that are directed towards teaching children and young people about food has been witnessed. Whilst there is much to learn about food, anxieties concerning the obesity epidemic have dramatically shaped how schools address the topic. This article draws on governmentality to consider 'the conditions of possibility' for teaching about food in contemporary times. In particular the form that knowledge about food takes in the midst of an obesity epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
3
24
0
2
Order By: Relevance
“…Their personal perspectives, as well as the resources and institutional norms, influence how adults -teachers or staff-approach the school meal (Leynse, 2008;Persson Osowski, Göranzon, & Fjellström, 2013). A focus on nutrition, for example, can give way to school food and school meals become a means to regulate, control and even punish students along with parents (Leahy & Wright, 2016;Pike & Leahy, 2012;Rich, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Their personal perspectives, as well as the resources and institutional norms, influence how adults -teachers or staff-approach the school meal (Leynse, 2008;Persson Osowski, Göranzon, & Fjellström, 2013). A focus on nutrition, for example, can give way to school food and school meals become a means to regulate, control and even punish students along with parents (Leahy & Wright, 2016;Pike & Leahy, 2012;Rich, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…as both the cause of and the solution to so many social ills' where 'class and wealth differences' can be overcome 'via proper cutlery and sitting around a table with good conversation'. Leahy and Wright (2016) argue the complexities of human relations to food are often overlooked in instrumentalist approaches to combat the obesity epidemic. They argue: 'The aesthetic, material, social, political and cultural complexities are removed and, within this biopedagogical mix, other ways of thinking about food, bodies and lives are subjugated ' (p. 244).…”
Section: The Research Contextmentioning
confidence: 99%
“…However, when the nutritional aspects of school food are the sole focus, there is a risk of downplaying the environmental and political dimensions; such as questions regarding how the consumption of animal bodies/products affects environmental degradation (Weaver-Hightower 2011; Rice and Rud 2018;Rice 2013Rice , 2017 and the life-and-death consequences for animals (Kahn 2010;Pedersen 2009). Researchers have also shown that when teachers educate students about food from a nutritional perspective they (often unintentionally) re-produce ideas of 'acceptable' or 'unacceptable' bodies (Leahy and Wright 2016;Pike and Kelly 2014;Russell and Semenko 2016). Collaborating with posthuman-pragmatist perspectives, Rowe (2016, 40) asserts that most of us, over a long time of years have established deep-seated patterns in the body that endorse the habit of meat eating.…”
Section: Moving From Nutritional To Environmental Ethical and Politimentioning
confidence: 99%